Existence of Coincidence and Fixed Point Theorems for Non-linear Hybrid Map on Generalized Space (Journal of Informatics and Mathematical Sciences, 2013)
In a recent paper Pathak et al. [20] established the coincidence and fixed point theorems for nonlinear hybrid contraction map under f-weak compatible continuous maps on metric spaces. In this paper we prove coincidence and fixed point theorems for nonlinear hybrid contraction maps on generalized metric spaces for multi-valued and single maps. Proved results of this paper to be a substantial generalization of the corresponding theorem of the recent paper [20].
Keywords: Generalized metric space; Fixed point; Hybrid contraction map; Multi-valued maps; Single maps